2010
DOI: 10.1007/s12665-010-0529-z
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and statistical approach to evaluate background concentrations of Cd, Cu, Pb and Zn (case study: Eastern Poland)

Abstract: . All the methods applied gave similar results. The highest deviation of the background was noted for Cu and the lowest for Zn. The lowest values of background were obtained for loess sediments and the highest in the case of the multiple 2r method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 19 publications
0
14
1
Order By: Relevance
“…The determined levels of the studied elements are not high in comparison with the values provided for the region by Lis and Pasieczna (1995) and Zgłobicki et al (2011), particularly in the case of copper and zinc. The geochemical background determined for the studied elements was similar for all three sites (Table 3).…”
Section: Resultscontrasting
confidence: 74%
“…The determined levels of the studied elements are not high in comparison with the values provided for the region by Lis and Pasieczna (1995) and Zgłobicki et al (2011), particularly in the case of copper and zinc. The geochemical background determined for the studied elements was similar for all three sites (Table 3).…”
Section: Resultscontrasting
confidence: 74%
“…The concentrations of trace elements in the bottom river sediments were mostly within the ranges typical of European background values (Table 1) (Kabata-Pendias and Pendias, 2001;Woitke et al, 2003;Zgłobicki et al, 2011), except for Zn, Ni and Cu whose values were above the background concentrations in most study sites (Zgłobicki et al, 2011). The pH of bottom sediments was close to neutral and ranged between 6.58 and 7.93.…”
Section: Resultsmentioning
confidence: 68%
“…Finally, results highlighted the importance of calculating background values for specific sites since the conditions and distribution of the parameters may be different and could lead to misinterpretations when assessing the degree of water alteration [17,22]. This was the case for coastal TP levels that exceed almost 100% with respect to the limits of Hawaii while background calculations suggested that levels were subject to natural increases that surpasses Hawaiian specific criteria for estuaries (3 NTU).…”
Section: Environmental Background Levelsmentioning
confidence: 97%